Evaluasi Kebijakan Ketenagakerjaan pada Upah Minimal dan Risiko Eksploitasi di Industri Formal - Restu Ramania (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The minimum wage is a labor policy instrument designed to protect workers from labor market failures and improve welfare. However, in practice, this policy still leaves room for labor exploitation in formal industries. This study aims to evaluate the effectiveness of labor policies on minimum wage setting and their implications for labor exploitation risks. This study uses a qualitative economic approach with a descriptive-analytical design based on secondary data. Data were obtained through a literature review of economic labor literature, statistical reports, and relevant previous research results. The results and discussion show that the minimum wage does not yet fully function as an instrument of welfare protection, but rather tends to be a maximum wage limit due to the weak bargaining position of workers and an unbalanced labor market structure. These conditions create economic dependence and increase vulnerability to exploitative labor practices even in the formal sector. The conclusion of this study emphasizes that strengthening minimum wage policies in line with the cost of living and productivity, supported by effective monitoring mechanisms, is necessary to reduce the risk of exploitation and promote the creation of a fair and sustainable labor market.